2007
DOI: 10.1021/ja068349v
|View full text |Cite
|
Sign up to set email alerts
|

Building Layer-by-Layer a Bis(dithiocarbamato)copper(II) Complex on Au{111} Surfaces

Abstract: A bis(dithiocarbamato)copper(II) complex (CuDTC2) was built on Au{111} surfaces (sheets and electrode beads) using different building blocks in a layer-by-layer (LbL) procedure. The process was followed by AFM and cyclic voltammetry. Initially 4-piperidinemethanethiol, which was synthesized here for the first time, was self-assembled on a gold surface and a highly organized array was obtained. The resulting monolayer was treated with CS2 and NH3 to transform the NH groups of piperidine into dithiocarbamate gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 20 publications
3
32
0
Order By: Relevance
“…The very negative reduction potential observed for CS 2 (−0.920 V) regarding the desorption of short thiol derivatives, such as mercaptopropanol (E p = −0.784 V [48]) or mercaptopropionic acid SAM (E = −0.800 V [49]), reveals the great stability of the resonant structure among the sulphur and carbon as the result of a good overlap of the orbitals of the ligand and the gold surface. In the case of the pure dithiocarbamate SAM reductive desorption, there is a shift of the potential towards positive direction most probably due to electron delocalisation between the resonant structure N-C(-S 2 ) which may lead to a weaker surface bond [24]. In fact, the desorption of the monolayer prepared by the surface reaction between gold, CS 2 and hexylmethylamine presents two reduction peaks, one more negative at −0.880 V, most probably associated with a fraction of CS 2 that was adsorbed and did not react with the amine, and the other less negative, at −0.800 V due to dithiocarbamate formation.…”
Section: Covalent Attachment Of Electroactive Compounds Containing Ammentioning
confidence: 99%
See 1 more Smart Citation
“…The very negative reduction potential observed for CS 2 (−0.920 V) regarding the desorption of short thiol derivatives, such as mercaptopropanol (E p = −0.784 V [48]) or mercaptopropionic acid SAM (E = −0.800 V [49]), reveals the great stability of the resonant structure among the sulphur and carbon as the result of a good overlap of the orbitals of the ligand and the gold surface. In the case of the pure dithiocarbamate SAM reductive desorption, there is a shift of the potential towards positive direction most probably due to electron delocalisation between the resonant structure N-C(-S 2 ) which may lead to a weaker surface bond [24]. In fact, the desorption of the monolayer prepared by the surface reaction between gold, CS 2 and hexylmethylamine presents two reduction peaks, one more negative at −0.880 V, most probably associated with a fraction of CS 2 that was adsorbed and did not react with the amine, and the other less negative, at −0.800 V due to dithiocarbamate formation.…”
Section: Covalent Attachment Of Electroactive Compounds Containing Ammentioning
confidence: 99%
“…DTCs have been commonly used as chelating ligands in coordination chemistry [22,23], and the formation of bis(dithiocarbamate)copper(II) complex built on Au (1 1 1) surfaces, using a layer-by-layer procedure has been reported [24]. It was also demonstrated that monolayers formed from lithium dioctadecyldithiocarbamate [21] display similar capacitance, thickness, crystallinity and wetability than equivalent alkanethiols, and that dithiocarbamates-gold linkages are not disrupted when SAMs are exposed to alkanethiols [25].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, the sulfur-gold system has been the focus of renewed attention in relation to the formation of self-assembled monolayers (SAMs) from alkane and aromatic thiols [6][7][8][9][10][11], dithiols [6] and dithiocarbamates [12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…4 In situ DTC formation has proven useful for anchoring a wide variety of amine-terminated molecules onto Au surfaces, ranging from low-molecular weight species to complex structures capable of biomolecular or supramolecular recognition. 4,5,6,7,8,9,10,11,12, 13,14,15,16,17,18,19 Recently, in situ DTC formation has been extended toward the chemisorptive anchoring of polymeric amines such as polyethyeleneimine (PEI). 20 …”
Section: Introductionmentioning
confidence: 99%